Studies On The Properties Of Hybrid Mineral Fillers Filled Polypropylene Composites - Vincent, Sheril Rizal (2013)
In the present study, properties of single composites (mica, silica, talc and CaCO3) and hybrids of silica/talc (SI/T), CaCO3/talc (CC/T), silica/mica (SI/M) and CaCO3/mica (CC/M) filled polypropylene (PP) composites were investigated. Due to the availability of local resources of mica filler in Malaysia, there is a possibility to replace the imported talc with mica. Hence in this study the properties of single PP composites, talc and mica hybrids filled PP composites at different filler ratio on the mechanical, thermal, flammability and rheological properties of PP composites were investigated. These hybrid composites systems were compounded using Haake internal mixer and hot compressed at 180 °C as per requirements for testing. In single mineral filler filled PP composites, mica showed better Young’s modulus compared to the other fillers and high tensile strength at high content of mica filler. CaCO3 filler demonstrated the highest values of impact strength compared to other types of fillers. In hybrid composites of SI/T and CC/T, CC/T system showed 11% increasing in Young’s modulus values with respect to the unfilled PP with increasing T. However, SI/T system has a decreasing trend of Young’s modulus. The same trend was observed in tensile strength, where CC/T hybrid composites showed increasing trend whilst SI/T hybrid composites exhibited a decreasing trend with every 10wt% increase of talc filler loading. CC/T composites also showed good thermal properties where it exhibits lower CTE values and higher thermal stability with high filler loading of talc. On the other hand, SI/T composites showed better impact strength and flammability if compared to CC/T composites. For hybrid composites of SI/M and CC/M, both composites have improved the stiffness with increasing amount of mica filler where CC/M composites demonstrated higher increment compared to SI/M composites.